Ternary positive electrode material, preparation method thereof and lithium ion battery
Through the core-protective layer-shell structural design, the problem of poor circulation and rate performance of single-crystal ternary cathode material is solved, and the mechanical strength and structural stability of the material are improved, which significantly extends its cycle life.
Patent Information
- Application Number
- CN202510008249.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The cycling and rate performance of the single crystal ternary cathode materials prepared in the prior art are poor.
The unique core-protective layer-shell structure design is adopted to increase the contact surface area with the electrolyte through the rich pore structure of the core, the protective layer enhances surface stability and electrolyte compatibility, the shell improves mechanical properties, and ensures the integrity of the material during the circulation process.
It significantly improves the rate performance and cycle life of the ternary positive electrode material, and improves the mechanical strength and structural stability of the material under high voltage application conditions.
Smart Images

Figure CN119812308A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a ternary positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] In today's society, with the increasing awareness of environmental protection, the development of new energy technology has become a global consensus. Lithium-ion batteries have been widely used in electric vehicles, 3C products, energy storage and other fields due to their high energy density and portability. As an indispensable energy supply device, lithium-ion battery technology has received widespread attention. Among them, the positive electrode material is one of its four core materials, and its performance directly determines the overall performance of the battery.
[0003] As the current mainstream lithium-ion cathode material, single-crystal ternary cathode materials have become the focus of in-depth research by scientific researchers due to their excellent energy density and cycle life. However, the traditionally prepared ternary single-crystal materials have certain limitations. The compactness of their internal structure and the scarcity of active sites limit the improvement of their rate performance.
[0004] Therefore, it is particularly important to conduct modification research on the structural characteristics of single-crystal ternary cathode materials. Current research focuses on two core issues: (1) How to enhance the single-particle mechanical strength of the material under high-voltage application conditions to ensure the integrity of the material during the cycle; (2) How to optimize the internal structure of the single-crystal material to create more active sites and provide a smoother channel for lithium ion diffusion, thereby ensuring sufficient infiltration of the electrolyte, further shortening the diffusion distance of lithium ions, and improving the rate performance of the material to meet application scenarios with higher performance requirements. This research direction is of great significance to promoting the advancement of lithium-ion battery technology. However, the cycle performance and rate performance of the single-crystal ternary cathode materials obtained by the existing preparation methods are still poor. Summary of the invention
[0005] The main purpose of the present invention is to provide a ternary positive electrode material and a preparation method thereof, and a lithium ion battery, so as to solve the problem that the single crystal ternary positive electrode material prepared in the prior art has poor cycle performance and rate performance.
[0006] In order to achieve the above object, according to one aspect of the present invention, a ternary cathode material is provided, the chemical formula of which is Li a Ni x Co y Mn z Me (1-x-y-z)O2, wherein 0.95≤a≤1.2, 0.65≤x≤1, 0<y≤1, 0<z≤1, x+y+z≤1; Me represents a doping element, and the doping element is selected from any one or more of Al, Ti, W, Zr, Mg, Nb, Co and Ca; the ternary positive electrode material includes a core and a protective layer and a shell layer sequentially coated on the surface of the core, and the protective layer is arranged in contact with the surface of the core; the porosity of the core is 40-60%.
[0007] This application effectively improves the mechanical strength and structural stability of the ternary positive electrode material under high voltage application conditions through a unique core-protective layer-shell structure design. Specifically, the rich pore structure of the core increases the contact surface area between the ternary positive electrode material and the electrolyte, thereby improving the lithium ion conduction efficiency. The protective layer further enhances the surface stability and electrolyte compatibility of the core. The design of the shell further enhances the mechanical properties of the ternary positive electrode material, ensures the integrity of the ternary positive electrode material during the cycle, thereby significantly improving the rate performance and cycle life of the ternary positive electrode material.
[0008] Furthermore, the volume ratio of the core, the protective layer and the shell layer is (40-80):(15-59):(1-5); and / or, the core and the shell layer are each independently a ternary material, and the chemical formula of the ternary material is Li b Ni n Co m Mn p M (1-n-m-p) O2, wherein 0.95≤b≤1.2, 0.65≤n≤1, 0<m≤1, 0<p≤1, n+m+p≤1, M represents a doping element, and the doping element is selected from any one or more of Al, Ti, W, Zr, Mg, Nb, Co and Ca; and / or the volume of the inner core is 40-80% of the total volume of the ternary positive electrode material; and / or the protective layer is lithium cobalt oxide.
[0009] Optimizing and controlling the mass ratio of the core, protective layer and shell layer within the above range, as well as controlling the chemical composition of the core and shell layer, is conducive to making the internal structure of the ternary material more reasonable, thereby optimizing the overall mechanical strength and chemical stability of the ternary cathode material, and thus improving the cycle stability and rate performance of the ternary cathode material as a whole. At the same time, the volume proportion of the core provides a large number of lithium ion transmission channels and stress release space, thereby increasing the active sites and promoting the full infiltration of the electrolyte.
[0010] Furthermore, the porosity of the ternary cathode material is 10-30%; and / or the pore volume of the ternary cathode material is 0.0100-0.1000cm 3 / g; and / or the particle size of the ternary positive electrode material is 1.5 to 3.5 μm, the average particle size D50 of the ternary positive electrode material is 2.0 to 5.0 μm, and the particle size distribution of the ternary positive electrode material is (D90-D10) / D50=0.6 to 1.4:1.
[0011] It is preferred to control the porosity, pore volume, particle size, average particle size and particle size distribution of the ternary positive electrode material within the above range, which is beneficial to increase the surface area of the ternary positive electrode material in contact with the electrolyte, shorten the diffusion distance of lithium ions, thereby improving the structural stability and lithium ion transmission efficiency of the ternary positive electrode material, ensuring the cycle stability and mechanical strength of the ternary positive electrode material under high voltage application, and thus improving the overall performance and safety of the battery.
[0012] According to another aspect of the present invention, a method for preparing the aforementioned ternary positive electrode material is provided, the preparation method comprising: step S1, mixing a first raw material comprising a core of the ternary positive electrode material and a sealing agent to obtain a first slurry; step S2, in an inert atmosphere, hydrothermally reacting a second raw material comprising the first slurry, a cobalt salt solution and a first precipitant to obtain a second slurry; step S3, performing a first coprecipitation reaction on a third raw material comprising the second slurry, a second precipitant, a first complexing agent, a first base solution and a first metal solution to obtain a first precipitate; step S4, in an oxygen atmosphere, performing a first sintering on a fourth raw material comprising the first precipitate, a first lithium salt and a modifying additive to obtain a ternary positive electrode material; wherein the porosity of the core of the ternary positive electrode material is 40 to 60%.
[0013] This application achieves efficient preparation of ternary cathode materials through specific steps and condition control; among them, the sealing agent effectively protects the pore structure of the core of the ternary cathode material from being destroyed in the subsequent preparation steps. The hydrothermal reaction and the first coprecipitation reaction successively form a protective layer and a shell layer on the surface of the core of the ternary cathode material, thereby optimizing the internal chemical composition and microstructure of the ternary cathode material. The first sintering further improves the mechanical properties and chemical stability of the ternary cathode material, thereby improving the structural stability and electrochemical properties of the obtained ternary cathode material, which is suitable for high-voltage lithium-ion battery applications.
[0014] Furthermore, the above-mentioned step S1 includes: mixing a sealing agent, a core of a ternary positive electrode material and a solvent to obtain a first slurry, wherein the solid content of the first slurry is 20 to 40%, and the solvent is selected from any one or more of ethanol, propanol, methanol and Tween 80; and / or, the mass ratio of the sealing agent to the core of the ternary positive electrode material is (20 to 40): (60 to 80), and the sealing agent is preferably polyurethane and / or polymethacrylate.
[0015] It is preferred to control the solid content of the first slurry and the selection of the solvent within the above range, which is conducive to more uniform mixing of the first raw material, thereby forming a stable first slurry, which is conducive to the formation and regulation of the particle structure in the subsequent steps. At the same time, by controlling the mass ratio of the sealing agent to the core of the ternary positive electrode material and the type of the sealing agent within the above range, it is conducive to fully protecting the pore structure in the core of the ternary positive electrode material.
[0016] Further, in the above step S2, in the second raw material, the concentration of the cobalt salt solution is 1.0-3.0 mol / L; and / or, the cobalt salt solution is selected from any one or more of cobalt sulfate solution, cobalt carbonate solution, cobalt chloride solution, and cobalt oxalate solution; and / or, the first precipitant is selected from any one or more of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and lithium hydroxide aqueous solution, and the mass concentration of the first precipitant is 20-50 wt%; and / or, the pH of the hydrothermal reaction is 9.5-11.5; and / or, the temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 8-12 h; and / or, the solid content of the second slurry is 200-600 g / L.
[0017] It is preferred to control the concentration and type of the cobalt salt solution and the type of the first precipitant within the above range, which is conducive to forming a cobalt hydroxide protective layer on the surface of the core of the ternary positive electrode material. Among them, the control of the hydrothermal reaction conditions is conducive to promoting the uniform formation of the protective layer, thereby improving the protective effect of the protective layer on the core of the ternary positive electrode material.
[0018] Furthermore, in the above step S3, the specific surface area of the first precipitate is 2 to 5 m 2 / g; and / or the tap density of the first precipitate is 1.6 to 2.2 g / cm 3 ; and / or the D50 particle size of the first precipitate is 2.5-6.0 μm; and / or the first base liquid is a mixed solution of sodium hydroxide and ammonia water, the pH value of the first base liquid is 12.0-13.0, and the concentration of ammonia water in the first base liquid is 0.3-1.5 g / L; and / or the total molar concentration of metal ions in the first metal salt solution is 1.0-3.0 mol / L; and / or the first precipitant is a metal hydroxide aqueous solution, preferably the metal hydroxide aqueous solution is selected from any one or more of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and lithium hydroxide aqueous solution; and / or the mass concentration of the first precipitant is 20-50 wt%; and / or the pH value of the first coprecipitation reaction is 11.50-12.50, and / or the temperature of the first coprecipitation reaction is 40-80° C.; and / or the first complexing agent is an ammonia aqueous solution of 8-20 mol / L, and the total mass concentration of ammonia water added to the first coprecipitation reaction is preferably 0.6-2.5 g / L.
[0019] It is preferred to control the physical properties and reaction conditions of the first precipitate within the above range, which is conducive to the formation of a shell material with high structural stability and ion conduction efficiency, while ensuring that the resulting material has a suitable porosity and pore volume, and is also conducive to the rapid diffusion of lithium ions and sufficient contact with the electrolyte, thereby improving the electrochemical performance of the ternary positive electrode material.
[0020] Furthermore, in the above step S4, the ratio of the total molar amount of nickel ions, cobalt ions, and manganese ions in the first metal solution to the molar amount of lithium ions in the first lithium salt is 1:1.0-1.20; and / or, the modifying additive is selected from any one or more of zirconium oxide, aluminum oxide, tungsten oxide, niobium oxide, strontium carbonate, calcium carbonate, cobalt hydroxide, titanium oxide, and magnesium oxide; and / or, the mass of the modifying additive is 0.01%-1% of the mass of the first precipitate; and / or, the temperature of the first sintering is 700-1000°C, and the holding time of the first sintering is 8-17h; and / or, the Rockwell hardness of the ternary positive electrode material is 10-40HRC.
[0021] It is preferred to control the molar ratio of metal ions to lithium ions within the above range, which is beneficial to improving the overall structural stability of the ternary cathode material and the insertion / deinsertion efficiency of lithium ions. By controlling the type and quality of the modifying additive within the above range, it is helpful to enrich the chemical composition and microstructure of the shell layer. By controlling the temperature and time of the first sintering within the above range, it is beneficial to improve the overall mechanical strength and chemical stability of the ternary cathode material, so that the final ternary cathode material exhibits excellent electrochemical performance and cycle stability.
[0022] Furthermore, the preparation method also includes a preparation process of the core of the ternary positive electrode material, which includes: in an inert atmosphere, a second coprecipitation reaction is carried out on the raw materials including the second metal solution, the third precipitant, the second complexing agent and the second base solution to obtain ternary precursor particles; in an oxygen atmosphere, a second sintering is carried out on the raw materials including the ternary precursor particles, the second lithium salt and the additive to obtain the core of the ternary positive electrode material; the specific surface area of the ternary precursor particles is 20 to 80 m 2 / g, and the tap density of the ternary precursor particles is 0.9-1.8 g / cm 3, the average particle size D50 of the ternary precursor particles is 8.0-17.0 μm; and / or, the total molar concentration of metal ions in the aqueous solution of the second metal salt is 1.0-3.0 mol / L, and the ratio of the total molar amount of nickel ions, cobalt ions, and manganese ions in the second metal solution to the molar amount of lithium ions in the second lithium salt is 1:1.0-1.20; and / or, the second base liquid is an ammonia solution, and the concentration of the second base liquid is 0.02-0.5 mol / L; and / or, the third precipitant is a sodium carbonate solution and / or a potassium carbonate solution, and the third precipitant is The concentration of the precipitating agent is 4-10 mol / L; and / or, the second complexing agent is an ammonia solution, and the concentration of the second complexing agent is 5-15 mol / L; and / or, the temperature of the second coprecipitation reaction is 40-80°C; and / or, the additive is selected from any one or more of zirconium oxide, aluminum oxide, tungsten oxide, niobium oxide, strontium carbonate, calcium carbonate and cobalt hydroxide, and the mass of the additive is 0.01%-1% of the mass of the ternary precursor particles; and / or, the temperature of the first sintering is 500-800°C, and the time of the first sintering is 5-12h.
[0023] The present application is conducive to the efficient preparation of a ternary positive electrode material core (composite basic carbonate precursor) with excellent pore structure through a second coprecipitation reaction carried out under an inert atmosphere and a second sintering step under an oxygen atmosphere. On the one hand, the porous structure of the core of the ternary positive electrode material increases its contact area with the electrolyte and improves the lithium ion transmission rate; on the other hand, it helps to release the cyclic crystal expansion stress and prevent particle cracking during the subsequent multi-stage sintering process. At the same time, relative to pure hydroxide precursors, composite basic carbonate precursors as cores can reduce production costs. At the same time, the range of the above-mentioned reaction conditions is optimized and controlled to ensure that the core material has high porosity, suitable tap density and particle size distribution, which is beneficial to lithium ion transmission and stress release during the cycle, and further improves the electrochemical properties and mechanical strength of the material.
[0024] Furthermore, the preparation method further includes: in an oxygen-containing atmosphere, performing a third sintering on the raw materials including the first sintered product obtained in step S4 and the coating agent to obtain a ternary positive electrode material; wherein the coating agent is selected from any one or more of zirconium oxide, titanium oxide, cobalt oxide, boric acid, aluminum oxide and tungsten oxide; and / or, the mass of the coating agent is 0.01% to 1% of the mass of the first precipitate; and / or, the oxygen concentration of the oxygen-containing atmosphere is 85 to 100%; and / or, the temperature of the third sintering is 250 to 800°C, and the time of the third sintering is 3 to 8 hours.
[0025] The present application is beneficial to improving the surface stability and chemical compatibility of the ternary positive electrode material by coating the first sintered product in an oxygen-containing atmosphere; preferably controlling the type and quality of the coating agent within the above range is helpful to form a stable protective layer on the surface of the ternary positive electrode material, thereby further enhancing the corrosion resistance and cycle stability of the ternary positive electrode material; by controlling the oxygen concentration of the oxygen-containing atmosphere and the temperature and time of the third sintering, the firmness of the coating layer bonded to the surface of the ternary positive electrode material is improved, thereby improving the overall electrical performance of the ternary positive electrode material.
[0026] According to another aspect of the present invention, a lithium-ion battery is provided, comprising a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode material, and the positive electrode material is the aforementioned ternary positive electrode material.
[0027] The lithium-ion battery including the above-mentioned ternary positive electrode material has excellent rate performance and cycle performance.
[0028] By applying the technical solution of the present invention, the present application effectively improves the mechanical strength and structural stability of the ternary positive electrode material under high voltage application conditions through a unique core-protective layer-shell structure design. Specifically, the rich pore structure of the core increases the contact surface area between the ternary positive electrode material and the electrolyte, thereby improving the lithium ion conduction efficiency. The protective layer further enhances the surface stability and electrolyte compatibility of the core. The design of the shell further enhances the mechanical properties of the ternary positive electrode material, ensures the integrity of the ternary positive electrode material during the cycle, thereby significantly improving the rate performance and cycle life of the ternary positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0030] Figure 1 The SEM image of the nickel-cobalt-manganese basic composite carbonate precursor prepared in Example 1 is shown;
[0031] Figure 2 The SEM image of the core of the ternary cathode material prepared in Example 1 is shown;
[0032] Figure 3 The cross-sectional SEM image of the core of the ternary cathode material prepared in Example 1 is shown;
[0033] Figure 4 The SEM image of the sintered product prepared in Example 1 is shown;
[0034] Figure 5 The SEM image of the ternary positive electrode material prepared in Example 1 is shown;
[0035] Figure 6 The cycle trend diagram of the ternary positive electrode material obtained in Example 1 and Comparative Example 1 is shown. DETAILED DESCRIPTION
[0036] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0037] As analyzed in the background technology of this application, the single-crystal ternary positive electrode material prepared in the prior art has the problem of poor cycle performance and rate performance. In order to solve this problem, this application provides a ternary positive electrode material and a preparation method thereof, and a lithium-ion battery.
[0038] In a typical embodiment of the present application, a ternary cathode material is provided, the chemical formula of which is Li a Ni x Co y Mn z Me (1-x-y-z) O2, wherein 0.95≤a≤1.2, 0.65≤x≤1, 0<y≤1, 0<z≤1, x+y+z≤1; Me represents a doping element, and the doping element is selected from any one or more of Al, Ti, W, Zr, Mg, Nb, Co and Ca; the ternary positive electrode material includes a core and a protective layer and a shell layer sequentially coated on the surface of the core, and the protective layer is arranged in contact with the surface of the core; the porosity of the core is 40-60%.
[0039] This application effectively improves the mechanical strength and structural stability of the ternary positive electrode material under high voltage application conditions through a unique core-protective layer-shell structure design. Specifically, the rich pore structure of the core increases the contact surface area between the ternary positive electrode material and the electrolyte, thereby improving the lithium ion conduction efficiency. The protective layer further enhances the surface stability and electrolyte compatibility of the core. The design of the shell further enhances the mechanical properties of the ternary positive electrode material, ensures the integrity of the ternary positive electrode material during the cycle, thereby significantly improving the rate performance and cycle life of the ternary positive electrode material.
[0040] In one embodiment of the present application, the volume ratio of the core, the protective layer and the shell layer is (40-80):(15-59):(1-5); and / or, the core and the shell layer are each independently a ternary material, and the chemical formula of the ternary material is Li b Ni n Co m Mn p M (1-n-m-p)O2, wherein 0.95≤b≤1.2, 0.65≤n≤1, 0<m≤1, 0<p≤1, n+m+p≤1, M represents a doping element, and the doping element is selected from any one or more of Al, Ti, W, Zr, Mg, Nb, Co and Ca; and / or the volume of the inner core is 40-80% of the total volume of the ternary positive electrode material; and / or the protective layer is lithium cobalt oxide.
[0041] Optimizing and controlling the mass ratio of the core, protective layer and shell layer within the above range, as well as controlling the chemical composition of the core and shell layer, is conducive to making the internal structure of the ternary material more reasonable, thereby optimizing the overall mechanical strength and chemical stability of the ternary cathode material, and thus improving the cycle stability and rate performance of the ternary cathode material as a whole. At the same time, the volume proportion of the core provides a large number of lithium ion transmission channels and stress release space, thereby increasing the active sites and promoting the full infiltration of the electrolyte.
[0042] In one embodiment of the present application, the porosity of the ternary positive electrode material is 10-30%; and / or the pore volume of the ternary positive electrode material is 0.0100-0.1000cm 3 / g; and / or the particle size of the ternary positive electrode material is 1.5 to 3.5 μm, the average particle size D50 of the ternary positive electrode material is 2.0 to 5.0 μm, and the particle size distribution of the ternary positive electrode material is (D90-D10) / D50=0.6 to 1.4:1.
[0043] It is preferred to control the porosity, pore volume, particle size, average particle size and particle size distribution of the ternary positive electrode material within the above range, which is beneficial to increase the surface area of the ternary positive electrode material in contact with the electrolyte, shorten the diffusion distance of lithium ions, thereby improving the structural stability and lithium ion transmission efficiency of the ternary positive electrode material, ensuring the cycle stability and mechanical strength of the ternary positive electrode material under high voltage application, and thus improving the overall performance and safety of the battery.
[0044] In another typical embodiment of the present application, a method for preparing a ternary positive electrode material is provided, the preparation method comprising: step S1, mixing a first raw material including a core of a ternary positive electrode material and a sealing agent to obtain a first slurry; step S2, in an inert atmosphere, hydrothermally reacting a second raw material including a first slurry, a cobalt salt solution and a first precipitant to obtain a second slurry; step S3, performing a first coprecipitation reaction on a third raw material including a second slurry, a second precipitant, a first complexing agent, a first base solution and a first metal solution to obtain a first precipitate; step S4, in an oxygen atmosphere, performing a first sintering on a fourth raw material including the first precipitate, a first lithium salt and a modifying additive to obtain a ternary positive electrode material; wherein the porosity of the core of the ternary positive electrode material is 40 to 60%.
[0045] This application achieves efficient preparation of ternary cathode materials through specific steps and condition control; among them, the sealing agent effectively protects the pore structure of the core of the ternary cathode material from being destroyed in the subsequent preparation steps. The hydrothermal reaction and the first coprecipitation reaction successively form a protective layer and a shell layer on the surface of the core of the ternary cathode material, thereby optimizing the internal chemical composition and microstructure of the ternary cathode material. The first sintering further improves the mechanical properties and chemical stability of the ternary cathode material, thereby improving the structural stability and electrochemical properties of the obtained ternary cathode material, which is suitable for high-voltage lithium-ion battery applications.
[0046] In one embodiment of the present application, the above-mentioned step S1 includes mixing a sealing agent, a core of a ternary positive electrode material and a solvent to obtain a first slurry, wherein the solid content of the first slurry is 20 to 40%, and the solvent is selected from any one or more of ethanol, propanol, methanol and Tween 80; and / or, the mass ratio of the sealing agent to the core of the ternary positive electrode material is (20 to 40): (60 to 80), and the sealing agent is preferably polyurethane and / or polymethacrylate.
[0047] It is preferred to control the solid content of the first slurry and the selection of the solvent within the above range, which is conducive to more uniform mixing of the first raw material, thereby forming a stable first slurry, which is conducive to the formation and regulation of the particle structure in the subsequent steps. At the same time, by controlling the mass ratio of the sealing agent to the core of the ternary positive electrode material and the type of the sealing agent within the above range, it is conducive to fully protecting the pore structure in the core of the ternary positive electrode material.
[0048] In one embodiment of the present application, in the above step S2, in the second raw material, the concentration of the cobalt salt solution is 1.0-3.0 mol / L; and / or, the cobalt salt solution is selected from any one or more of cobalt sulfate solution, cobalt carbonate solution, cobalt chloride solution, and cobalt oxalate solution; and / or, the first precipitant is selected from any one or more of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and lithium hydroxide aqueous solution, and the mass concentration of the first precipitant is 20-50 wt%; and / or, the pH of the hydrothermal reaction is 9.5-11.5; and / or, the temperature of the hydrothermal reaction is 100-200° C., and the time of the hydrothermal reaction is 8-12 h; and / or, the solid content of the second slurry is 200-600 g / L.
[0049] It is preferred to control the concentration and type of the cobalt salt solution and the type of the first precipitant within the above range, which is conducive to forming a cobalt hydroxide protective layer on the surface of the core of the ternary positive electrode material. Among them, the control of the hydrothermal reaction conditions is conducive to promoting the uniform formation of the protective layer, thereby improving the protective effect of the protective layer on the core of the ternary positive electrode material.
[0050] In one embodiment of the present application, in the above step S3, the specific surface area of the first precipitate is 2 to 5 m 2 / g; and / or the tap density of the first precipitate is 1.6 to 2.2 g / cm 3 ; and / or the D50 particle size of the first precipitate is 2.5-6.0 μm; and / or the first base liquid is a mixed solution of sodium hydroxide and ammonia water, the pH value of the first base liquid is 12.0-13.0, and the concentration of ammonia water in the first base liquid is 0.3-1.5 g / L; and / or the total molar concentration of metal ions in the first metal salt solution is 1.0-3.0 mol / L; and / or the first precipitant is a metal hydroxide aqueous solution, preferably the metal hydroxide aqueous solution is selected from any one or more of sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, and lithium hydroxide aqueous solution; and / or the mass concentration of the first precipitant is 20-50 wt%; and / or the pH value of the first coprecipitation reaction is 11.50-12.50, and / or the temperature of the first coprecipitation reaction is 40-80° C.; and / or the first complexing agent is an ammonia aqueous solution of 8-20 mol / L, and the total mass concentration of ammonia water added to the first coprecipitation reaction is preferably 0.6-2.5 g / L.
[0051] It is preferred to control the physical properties and reaction conditions of the first precipitate within the above range, which is conducive to the formation of a shell material with high structural stability and ion conduction efficiency, while ensuring that the resulting material has a suitable porosity and pore volume, and is also conducive to the rapid diffusion of lithium ions and sufficient contact with the electrolyte, thereby improving the electrochemical performance of the ternary positive electrode material.
[0052] In one embodiment of the present application, in the above step S4, the ratio of the total molar amount of nickel ions, cobalt ions, and manganese ions in the first metal solution to the molar amount of lithium ions in the first lithium salt is 1:1.0-1.20; and / or, the modifying additive is selected from any one or more of zirconium oxide, aluminum oxide, tungsten oxide, niobium oxide, strontium carbonate, calcium carbonate, cobalt hydroxide, titanium oxide and magnesium oxide; and / or, the mass of the modifying additive is 0.01%-1% of the mass of the first precipitate; and / or, the temperature of the first sintering is 700-1000°C, and the holding time of the first sintering is 8-17h; and / or, the Rockwell hardness of the ternary positive electrode material is 10-40HRC.
[0053] It is preferred to control the molar ratio of metal ions to lithium ions within the above range, which is beneficial to improving the overall structural stability of the ternary cathode material and the insertion / deinsertion efficiency of lithium ions. By controlling the type and quality of the modifying additive within the above range, it is helpful to enrich the chemical composition and microstructure of the shell layer. By controlling the temperature and time of the first sintering within the above range, it is beneficial to improve the overall mechanical strength and chemical stability of the ternary cathode material, so that the final ternary cathode material exhibits excellent electrochemical performance and cycle stability.
[0054] In one embodiment of the present application, the above-mentioned preparation method also includes a preparation process of the core of the ternary positive electrode material, and the preparation process includes: in an inert atmosphere, a second coprecipitation reaction is carried out on the raw materials including the second metal solution, the third precipitant, the second complexing agent and the second base liquid to obtain ternary precursor particles; in an oxygen atmosphere, a second sintering is carried out on the raw materials including the ternary precursor particles, the second lithium salt and the additive to obtain the core of the ternary positive electrode material; the specific surface area of the ternary precursor particles is 20 to 80 m 2 / g, and the tap density of the ternary precursor particles is 0.9-1.8 g / cm 3 , the average particle size D50 of the ternary precursor particles is 8.0-17.0 μm; and / or, the total molar concentration of metal ions in the aqueous solution of the second metal salt is 1.0-3.0 mol / L, and the ratio of the total molar amount of nickel ions, cobalt ions, and manganese ions in the second metal solution to the molar amount of lithium ions in the second lithium salt is 1:1.0-1.20; and / or, the second base liquid is an ammonia solution, and the concentration of the second base liquid is 0.02-0.5 mol / L; and / or, the third precipitant is a sodium carbonate solution and / or a potassium carbonate solution, and the third precipitant is The concentration of the precipitating agent is 4-10 mol / L; and / or, the second complexing agent is an ammonia solution, and the concentration of the second complexing agent is 5-15 mol / L; and / or, the temperature of the second coprecipitation reaction is 40-80°C; and / or, the additive is selected from any one or more of zirconium oxide, aluminum oxide, tungsten oxide, niobium oxide, strontium carbonate, calcium carbonate and cobalt hydroxide, and the mass of the additive is 0.01%-1% of the mass of the ternary precursor particles; and / or, the temperature of the first sintering is 500-800°C, and the time of the first sintering is 5-12h.
[0055] The present application is conducive to the efficient preparation of a ternary positive electrode material core (composite basic carbonate precursor) with excellent pore structure through a second coprecipitation reaction carried out under an inert atmosphere and a second sintering step under an oxygen atmosphere. On the one hand, the porous structure of the core of the ternary positive electrode material increases its contact area with the electrolyte and improves the lithium ion transmission rate; on the other hand, it helps to release the cyclic crystal expansion stress and prevent particle cracking during the subsequent multi-stage sintering process. At the same time, relative to pure hydroxide precursors, composite basic carbonate precursors as cores can reduce production costs. At the same time, the range of the above-mentioned reaction conditions is optimized and controlled to ensure that the core material has high porosity, suitable tap density and particle size distribution, which is beneficial to lithium ion transmission and stress release during the cycle, and further improves the electrochemical properties and mechanical strength of the material.
[0056] In one embodiment of the present application, the above-mentioned preparation method also includes: in an oxygen-containing atmosphere, performing a third sintering on the raw materials including the first sintered product obtained in step S4 and the coating agent to obtain a ternary positive electrode material; wherein the coating agent is selected from any one or more of zirconium oxide, titanium oxide, cobalt oxide, boric acid, aluminum oxide and tungsten oxide; and / or, the mass of the coating agent is 0.01% to 1% of the mass of the first precipitate; and / or, the oxygen concentration of the oxygen-containing atmosphere is 85 to 100%; and / or, the temperature of the third sintering is 250 to 800°C, and the time of the third sintering is 3 to 8 hours.
[0057] The present application is beneficial to improving the surface stability and chemical compatibility of the ternary positive electrode material by coating the first sintered product in an oxygen-containing atmosphere; preferably controlling the type and quality of the coating agent within the above range is helpful to form a stable protective layer on the surface of the ternary positive electrode material, thereby further enhancing the corrosion resistance and cycle stability of the ternary positive electrode material; by controlling the oxygen concentration of the oxygen-containing atmosphere and the temperature and time of the third sintering, the firmness of the coating layer bonded to the surface of the ternary positive electrode material is improved, thereby improving the overall electrical performance of the ternary positive electrode material.
[0058] In another typical embodiment of the present application, a lithium-ion battery is provided, including a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet includes a positive electrode material, and the positive electrode material is the above-mentioned ternary positive electrode material.
[0059] The lithium-ion battery including the above-mentioned ternary positive electrode material has excellent rate performance and cycle performance.
[0060] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0061] Example 1
[0062] The single crystal high voltage inner pore structure ternary cathode material is prepared according to the following steps:
[0063] Step (1): dissolve nickel sulfate, cobalt sulfate and manganese sulfate in deionized water in a molar ratio of nickel, cobalt and manganese of 65:7:28 to prepare a first metal salt solution with a concentration of 2.1 mol / L. In a reactor with deionized water, add sodium carbonate solution and ammonia water as the base solution, adjust the pH to 7.7, the ammonia concentration to 3.2 g / L, maintain the reactor temperature at 40°C, and maintain the speed at 1500 r / min. Then, in an inert atmosphere, continuously add the first metal salt solution prepared in step (1), a sodium carbonate solution of 4 g / L as a precipitant, and a 14 mol / L ammonia water as a complexing agent to the reactor, adjust the pH to 7.2, and keep the ammonia concentration within the range of 6.0 g / L, and stop the reaction when the solid particles D50 grow to 14.0 μm.
[0064] The slurry obtained above was aged, filtered, washed and dried in sequence to obtain a nickel-cobalt-manganese basic composite carbonate precursor. The solid particle D50 was tested to be 14.20 μm and the specific surface area was 20.56 m 2 / g, tap density 1.79g / cm 3 The test morphology of the nickel-cobalt-manganese basic composite carbonate precursor is as follows: Figure 1 shown.
[0065] Step (2): lithium hydroxide: nickel cobalt manganese basic composite carbonate precursor is added to a high-speed mixer in a molar ratio of lithium hydroxide: nickel cobalt manganese basic composite carbonate precursor = 1.06:1, and niobium oxide and tungsten oxide are added at 0.05% of the mass ratio of the nickel cobalt manganese basic composite carbonate precursor, respectively, and the mixture is fully mixed to obtain a first mixture.
[0066] Step (3): In an oxygen atmosphere, the first mixture is sintered in a roller kiln at a sintering temperature of 650° C. for 9 h to obtain a core of a ternary positive electrode material, the SEM image of which is shown in FIG. Figure 2 As shown, the cross-sectional SEM image of the core of the ternary cathode material is as follows Figure 3 shown.
[0067] Step (4): In a 10L reactor, add 10L of ethanol and 3kg of the ternary cathode material core obtained in step (3) to control the solid content to 300g / L, adjust the reactor speed to 1500r / min, then add 900g of polyurethane, stir for 5h, and filter to obtain the first slurry.
[0068] Step (5): In a 10L reactor, the first slurry obtained in step (4) is diluted to 400g / L with deionized water, and a 40% mass fraction of sodium hydroxide solution is added to adjust the pH in the reactor to 10.0-10.3, the rotation speed is controlled at 800r / min, and then 2.1mol / L cobalt sulfate solution is gradually added, and the temperature in the reactor is maintained at 140°C for 8h to obtain a second slurry.
[0069] Step (6): The second slurry obtained in step (5) is used as the base liquid, and 14 mol / L ammonia water is added to adjust the pH value to 12.5, and the ammonia concentration of the base liquid is 1.2 g / L, and the temperature is maintained at 60°C, and the rotation speed is controlled at 1500 r / min.
[0070] Then, under an inert atmosphere, the second metal salt solution, a sodium hydroxide solution with a precipitant mass fraction of 40%, and a complexing agent 14 mol / L ammonia water were continuously added to the reactor, and the rotation speed was reduced to 1000 r / min to carry out a co-precipitation reaction until the solid particles D50 grew to 3.4 μm, and the reaction was stopped.
[0071] The slurry obtained above was aged, filtered, washed and dried in sequence to obtain a first precipitate. The D50 of the first precipitate was 3.42 μm and the specific surface area was 9.89 m 2 / g, tap density is 1.89g / cm 3 .
[0072] Step (7): lithium hydroxide and the first precipitate are added to a high-speed mixer in a molar ratio of lithium hydroxide: (nickel + cobalt + manganese) = 1.08:1, and strontium carbonate and zirconium oxide are added at 0.2% of the mass ratio of the first precipitate, respectively. After being fully mixed, a mixture is obtained, which is loaded into a sagger to form a 5 cm high material layer. The material layer is cut into square sizes with an upper surface of 2 cm*2 cm using a mold, and the spacing between two adjacent blocks, i.e., the block gap, is 0.3 cm. The material is then placed in an atmosphere kiln and sintered at 850°C in an oxygen atmosphere and kept warm for 10 hours. The Rockwell hardness is tested to be 35HRC. After being coarsely crushed by two-stage rollers with an upper gap of 7 mm and a lower gap of 2 mm, air flow milling is performed to control the particle size D50 to be 3.0 μm to obtain a sintered product with a morphology as shown in the following example. Figure 4 shown.
[0073] Step (8): Add the sintered product obtained in step 7 to a high-speed mixer, and weigh 0.05% tungsten oxide and 0.10% aluminum oxide according to their mass fractions. After mixing evenly, sinter in a kiln under an oxygen atmosphere at a sintering temperature of 720°C for 6 hours. After cooling, remove the magnetism and screen to obtain a single-crystal high-voltage internal pore structure ternary positive electrode material, the SEM image of which is as follows: Figure 5 shown.
[0074] Example 2
[0075] The single crystal high voltage inner pore structure ternary cathode material is prepared according to the following steps:
[0076] Step (1): dissolving nickel sulfate, cobalt sulfate and manganese sulfate in deionized water at a molar ratio of nickel, cobalt and manganese of 65:7:28 to prepare a first metal salt solution with a concentration of 2.1 mol / L. In a reactor containing deionized water, adding sodium carbonate solution and ammonia water as a base solution, adjusting the pH to 8.0, the ammonia concentration to 3.2 g / L, maintaining the reactor temperature at 40°C, and the rotation speed at 1500 r / min. Then, in an inert atmosphere, continuously adding the first metal salt solution prepared in step (1), a precipitant 4 g / L sodium carbonate solution, and a complexing agent 14 mol / L ammonia water to the reactor, adjusting the pH to 7.5, and maintaining the ammonia concentration within the range of 6.5 g / L, and stopping the reaction when the solid particles D50 grow to 14.20 μm.
[0077] The slurry obtained above was aged, filtered, washed and dried in sequence to obtain a nickel-cobalt-manganese basic composite carbonate precursor. The solid particle D50 was tested to be 14.20 μm and the specific surface area was 20.56 m 2 / g, tap density 1.79g / cm 3 .
[0078] Step (2): lithium hydroxide: nickel cobalt manganese basic composite carbonate precursor is added to a high-speed mixer in a molar ratio of lithium hydroxide: nickel cobalt manganese basic composite carbonate precursor = 1.06:1, and niobium oxide and tungsten oxide are added at 0.05% of the mass ratio of the nickel cobalt manganese basic composite carbonate precursor, respectively, and the mixture is fully mixed to obtain a first mixture.
[0079] Step (3): In an oxygen atmosphere, the first mixture is placed in a roller kiln for sintering at a sintering temperature of 650° C. for a sintering time of 9 hours to obtain a core of the ternary positive electrode material.
[0080] Step (4): In a 10L reactor, add 10L of ethanol and 3kg of the ternary cathode material core obtained in step (3) to control the solid content to 300g / L, adjust the speed of the reactor to 1500r / min, then add 1000g of polyurethane, stir for 5h, and filter to obtain the first slurry;
[0081] Step (5): In a 10L reactor, the first slurry obtained in step (4) was diluted to 400 g / L with deionized water, and a 40% mass fraction of sodium hydroxide solution was added to adjust the pH in the reactor to 10.3, the rotation speed was controlled at 800 r / min, and then 2.1 mol / L cobalt sulfate solution was gradually added, and the temperature in the reactor was maintained at 140° C. for 8 hours to obtain a second slurry.
[0082] Step (6): The second slurry obtained in step (5) is used as the base liquid, and 14 mol / L ammonia water is added to adjust the pH value to 12.8, and the ammonia concentration of the base liquid is 1.2 g / L, and the temperature is maintained at 60°C, and the rotation speed is controlled at 1500 r / min.
[0083] Then, under an inert atmosphere, the second metal salt solution, the sodium hydroxide solution with a mass fraction of 40% of the precipitant, and the complexing agent 14 mol / L ammonia water were continuously added to the reactor, and the rotation speed was reduced to 1000 r / min to carry out a coprecipitation reaction until the solid particles D50 grew to 3.6 μm, and the reaction was stopped;
[0084] The slurry obtained above was aged, filtered, washed and dried in sequence to obtain a first precipitate. The D50 of the first precipitate was 3.42 μm and the specific surface area was 9.89 m 2 / g, tap density is 1.89g / cm 3 .
[0085] Step (7): adding lithium hydroxide and the first precipitate into a high-speed mixer in a molar ratio of lithium hydroxide: (nickel + cobalt + manganese) = 1.08:1, and adding strontium carbonate and zirconium oxide at 0.2% of the mass ratio of the first precipitate, respectively. After fully mixing, a mixture is obtained, which is loaded into a sagger to form a 5 cm high material layer, and the material layer is cut into square sizes with an upper surface of 2 cm*2 cm using a mold, and the spacing between two adjacent blocks, i.e., the block gap, is 0.3 cm. Then, the mixture is put into an atmosphere kiln, sintered at 850°C in an oxygen atmosphere, and kept warm for 10 hours to obtain a solid particle agglomerate. The Rockwell hardness of the solid particle agglomerate is tested to be 35HRC. After being coarsely crushed by two-stage rollers with an upper gap of 7 mm and a lower gap of 2 mm, the solid particle agglomerate is crushed by air flow to control the particle size D50 to 3.0-4.0 μm to obtain a sintered product.
[0086] Step (8): Add the sintered product obtained in step 7 into a high-speed mixer, and weigh 0.05% tungsten oxide and 0.10% aluminum oxide according to their mass fractions. After mixing evenly, sinter in a kiln under an oxygen atmosphere at a temperature of 720°C. Keep warm for 6 hours. After cooling, demagnetize and screen to obtain a single-crystal high-voltage internal porous structure ternary positive electrode material.
[0087] Example 3
[0088] The single crystal high voltage inner pore structure ternary cathode material is prepared according to the following steps:
[0089] Step (1): dissolve nickel sulfate, cobalt sulfate and manganese sulfate in deionized water in a molar ratio of nickel, cobalt and manganese of 65:7:28 to prepare a first metal salt solution with a concentration of 2.1 mol / L. In a reactor with deionized water, add sodium carbonate solution and ammonia water as the base solution, adjust the pH to 7.8, the ammonia concentration to 3.2 g / L, maintain the reactor temperature at 40°C, and maintain the speed at 1500 r / min. Then, in an inert atmosphere, continuously add the first metal salt solution prepared in step (1), a sodium carbonate solution of 4 g / L as a precipitant, and a 14 mol / L ammonia water as a complexing agent to the reactor, adjust the pH to 7.4, and keep the ammonia concentration within the range of 6.3 g / L, and stop the reaction when the solid particles D50 grow to 14.10 μm.
[0090] The slurry obtained above was aged, filtered, washed and dried in sequence to obtain a nickel-cobalt-manganese basic composite carbonate precursor. The solid particle D50 was tested to be 14.20 μm and the specific surface area was 20.56 m 2 / g, tap density 1.79g / cm 3 .
[0091] Step (2): adding lithium hydroxide: nickel cobalt manganese basic composite carbonate precursor into a high-speed mixer in a molar ratio of lithium hydroxide: nickel cobalt manganese basic composite carbonate precursor = 1.06:1, and simultaneously adding niobium oxide and tungsten oxide at a mass ratio of 0.05% of the nickel cobalt manganese basic composite carbonate precursor, respectively, and mixing thoroughly to obtain a first mixture;
[0092] Step (3): sintering the first mixture in a roller kiln in an oxygen atmosphere at a sintering temperature of 650° C. for 9 hours to obtain a core of the ternary positive electrode material.
[0093] Step (4): In a 10L reactor, add 10L of ethanol and 3kg of the ternary cathode material core obtained in step (3) to control the solid content to 300g / L, adjust the reactor speed to 1500r / min, then add 1000g of polyurethane, stir for 5h, and filter to obtain the first slurry.
[0094] Step (5): In a 10L reactor, the first slurry obtained in step (4) was diluted to 400 g / L with deionized water, and a 40% mass fraction of sodium hydroxide solution was added to adjust the pH in the reactor to 10.1, the rotation speed was controlled at 800 r / min, and then 2.1 mol / L cobalt sulfate solution was gradually added, and the temperature in the reactor was maintained at 140° C. for 8 hours to obtain a second slurry.
[0095] Step (6): The second slurry obtained in step (5) is used as the base liquid, and 14 mol / L ammonia water is added to adjust the pH value to 12.6, and the ammonia concentration of the base liquid is 1.2 g / L, and the temperature is maintained at 60°C, and the rotation speed is controlled at 1500 r / min.
[0096] Then, under an inert atmosphere, the second metal salt solution, a sodium hydroxide solution with a mass fraction of 40% as a precipitant, and a 14 mol / L ammonia water as a complexing agent were continuously added to the reactor, and the rotation speed was reduced to 1000 r / min to carry out a coprecipitation reaction until the solid particles D50 grew to 3.5 μm, and the reaction was stopped;
[0097] The slurry obtained above was aged, filtered, washed and dried in sequence to obtain the first precipitate. The solid particles D50 was 3.42 μm and the specific surface area was 9.89 m 2 / g, tap density is 1.89g / cm 3 .
[0098] Step (7): adding lithium hydroxide and the first precipitate to a high-speed mixer in a molar ratio of lithium hydroxide: (nickel + cobalt + manganese) = 1.08:1, and adding strontium carbonate and zirconium oxide at 0.2% of the mass ratio of the first precipitate, respectively, and mixing them thoroughly to obtain a mixture, which is then placed in a sagger to form a 5 cm high material layer, and the material layer is cut into squares with an upper surface of 2 cm*2 cm using a mold, and the spacing between two adjacent blocks, i.e., the block gap, is 0.3 cm, and then placed in an atmosphere kiln, sintered at 850° C. in an oxygen atmosphere, and kept warm for 10 hours to obtain a solid particle agglomerate, and its Rockwell hardness is tested to be 35 HRC, and after being coarsely crushed by two-stage rollers with an upper gap of 7 mm and a lower gap of 2 mm, air flow milling is performed to control the particle size D50 to 3.7 μm, and a sintered product is obtained;
[0099] Step (8): adding the sintered product obtained in step 7 to a high-speed mixer, and adding 0.05% tungsten oxide and 0.10% aluminum oxide according to their mass fractions, mixing well, and sintering in a kiln under an oxygen atmosphere at a sintering temperature of 720° C. for 6 hours. After cooling, demagnetizing and screening to obtain a single-crystal high-voltage internal porous structure ternary positive electrode material;
[0100] Example 4
[0101] The difference from Example 1 is that step (8) is not performed to obtain a ternary positive electrode material.
[0102] Example 5
[0103] The difference from Example 1 is that the mass of the sealing agent is 30% of the mass of the ternary positive electrode material, and a ternary positive electrode material is obtained.
[0104] Example 6
[0105] The difference from Example 1 is that the concentration of the cobalt sulfate solution is 3.0 mol / L, and a ternary positive electrode material is obtained.
[0106] Example 7
[0107] The difference from Example 1 is that the concentration of the cobalt sulfate solution is 0.8 mol / L, and a ternary positive electrode material is obtained.
[0108] Comparative Example 1
[0109] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a solution at a molar ratio of 2.1 mol / L and 50:20:30. Deionized water, 40% sodium hydroxide solution and 14 mol / L ammonia water were added to a 100 L reactor. The pH value was adjusted to 12.5-12.8, and the concentration of bottom liquid ammonia water was 1.2 g / L. The temperature was maintained at 60°C and the rotation speed was controlled at 1500 r / min.
[0110] Afterwards, under an inert atmosphere, the first metal salt solution, a sodium hydroxide solution with a mass fraction of 40% of the precipitant, and a 14 mol / L ammonia water as a complexing agent were continuously added to the reactor, and the pH was gradually reduced to 12.0 within 4 hours, and the ammonia concentration was controlled within the range of 1.8 to 2.0 g / L. When the solid particles D50 grew to 2.0 μm, the rotation speed was reduced to 1000 r / min, and the coprecipitation reaction was continued until the solid particles D50 grew to 3.4 μm, and the reaction was stopped.
[0111] The slurry obtained above was aged, filtered, washed and dried in sequence to obtain a nickel-cobalt-manganese hydroxide precursor. The solid particles D50 was tested to be 3.42 μm and the specific surface area was 9.89 m 2 / g, tap density is 1.89g / cm 3 .
[0112] Lithium carbonate: nickel cobalt manganese hydroxide precursor = 1.01:1 was added to a high mixer, and strontium carbonate and zirconium oxide were added at a mass ratio of 0.2% of nickel cobalt manganese hydroxide, respectively. After fully mixing, a mixture was obtained, which was loaded into a sagger to form a 5 cm high material layer. A mold was used to cut the material layer into square sizes with an upper surface of 2 cm*2 cm. The distance between two adjacent blocks, i.e., the block gap, was 0.3 cm. The blocks were then placed in an atmosphere kiln and sintered at 850°C in an oxygen atmosphere for 10 hours.
[0113] After the obtained single crystal layer agglomerate was taken out, its hardness was tested to be 50HRC. After being roughly crushed by two-stage rollers with an upper gap of 7mm and a lower gap of 2mm, it was air flow crushed and the particle size D50 was controlled to be 3.0-4.0μm to obtain a ternary positive electrode material. Its average particle size was measured to be 2.1μm, and the particle size distribution (D90-D10) / D50 value was 1.1. Its cycle trend diagram is shown in the attached figure. Figure 6 shown.
[0114] Comparative Example 2
[0115] The difference from Example 1 is that step (4) is not performed to obtain a ternary positive electrode material.
[0116] Comparative Example 3
[0117] The difference from Example 1 is that step (5) is not performed to obtain a ternary positive electrode material.
[0118] Comparative Example 4
[0119] The difference from Example 1 is that steps (6) and (7) are not performed to obtain a ternary positive electrode material.
[0120] Comparative Example 5
[0121] The difference from Example 1 is that the porosity of the inner core of the ternary positive electrode material is 30%, and a ternary positive electrode material is obtained.
[0122] The ternary positive electrode materials obtained in the above embodiments and comparative examples are prepared into electrode plates. In the preparation of the plates, the mass ratio of the ternary positive electrode material, the conductive agent and the binder is 90:5:5, wherein the conductive agent is acetylene carbon black, the binder is polyvinylidene fluoride, the solvent is N-methylpyrrolidone, the current collector is aluminum foil, and the lithium sheet is used as the negative electrode. The electrolyte composition is as follows: ethylene carbonate: ethyl methyl carbonate = 3:7, the lithium salt is 1M lithium hexafluorophosphate, the additive is 2.0% vinylene carbonate, and the separator The electrode pieces are assembled into 2016-type button cells, and then the electrochemical performance of the cells is tested. The test temperature is a 25°C constant temperature cabinet, and the rate test schemes are 0.2C charge / 0.2C discharge, 0.33C charge / 0.33C discharge, 1C charge / 1C discharge, and then 0.5C charge / 1C discharge cycles. The test voltage range is 2.8-4.5V. The test results are shown in Table 1 below. The cycle trend diagrams of the ternary positive electrode materials obtained in Example 1 and Comparative Example 1 are shown in the attached figure. Figure 6 shown.
[0123] Table 1
[0124]
[0125]
[0126] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0127] This application effectively improves the mechanical strength and structural stability of the ternary positive electrode material under high voltage application conditions through a unique core-protective layer-shell structure design. Specifically, the rich pore structure of the core increases the contact surface area between the ternary positive electrode material and the electrolyte, thereby improving the lithium ion conduction efficiency. The protective layer further enhances the surface stability and electrolyte compatibility of the core. The design of the shell further enhances the mechanical properties of the ternary positive electrode material, ensures the integrity of the ternary positive electrode material during the cycle, thereby significantly improving the rate performance and cycle life of the ternary positive electrode material.
[0128] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A ternary positive electrode material, characterized in that: The chemical formula of the ternary cathode material is Li a Ni x Co y Mn z Me (1-x-y-z) O2, where 0.95≤a≤1.2, 0.65≤x≤1, 0<y≤1, 0<z≤1, x+y+z≤1; Me represents a doping element, and the doping element is selected from any one or more of Al, Ti, W, Zr, Mg, Nb, Co and Ca; the ternary positive electrode material includes a core and a protective layer and a shell layer sequentially coated on the surface of the core, and the protective layer is arranged in contact with the surface of the core; the porosity of the core is 40-60%.
2. The ternary positive electrode material according to claim 1, characterized in that: The volume ratio of the core, the protective layer and the shell layer is (40-80):(15-59):(1-5); and / or, the core and the shell layer are each independently a ternary material, and the chemical formula of the ternary material is Li b Ni n Co m Mn p M (1-n-m-p) O2, wherein 0.95≤b≤1.2, 0.65≤n≤1, 0<m≤1, 0<p≤1, n+m+p≤1, M represents a doping element, and the doping element is selected from any one or more of Al, Ti, W, Zr, Mg, Nb, Co and Ca; and / or the volume of the inner core is 40-80% of the total volume of the ternary positive electrode material; and / or the protective layer is lithium cobalt oxide.
3. The ternary positive electrode material according to claim 1 or 2, characterized in that: The porosity of the ternary positive electrode material is 10-30%; and / or the pore volume of the ternary positive electrode material is 0.0100-0.1000cm 3 / g; and / or the particle size of the ternary positive electrode material is 1.5 to 3.5 μm, the average particle size D50 of the ternary positive electrode material is 2.0 to 5.0 μm, and the particle size distribution of the ternary positive electrode material is (D90-D10) / D50=0.6 to 1.4:
1.
4. A method for preparing the ternary positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, mixing a first raw material including a ternary positive electrode material core and a sealing agent to obtain a first slurry; Step S2, in an inert atmosphere, subjecting a second raw material including the first slurry, a cobalt salt solution and a first precipitant to a hydrothermal reaction to obtain a second slurry; Step S3, subjecting a third raw material including the second slurry, the second precipitant, the first complexing agent, the first base solution and the first metal solution to a first coprecipitation reaction to obtain a first precipitate; Step S4, in an oxygen atmosphere, performing a first sintering on a fourth raw material including the first precipitate, the first lithium salt and the modifying additive to obtain the ternary positive electrode material; Wherein, the porosity of the inner core of the ternary positive electrode material is 40-60%.
5. The preparation method according to claim 4, characterized in that: The step S1 comprises: The sealing agent, the core of the ternary cathode material and a solvent are mixed to obtain the first slurry, wherein the solid content of the first slurry is 20-40%, and the solvent is selected from any one or more of ethanol, propanol, methanol and Tween 80; And / or, the mass ratio of the sealing agent to the inner core of the ternary positive electrode material is (20-40):(60-80), and preferably the sealing agent is polyurethane and / or polymethacrylate.
6. The preparation method according to claim 4 or 5, characterized in that: In the step S2, the concentration of the cobalt salt solution in the second raw material is 1.0 to 3.0 mol / L; And / or, the cobalt salt solution is selected from any one or more of a cobalt sulfate solution, a cobalt carbonate solution, a cobalt chloride solution, and a cobalt oxalate solution; And / or, the first precipitant is selected from any one or more of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, and a lithium hydroxide aqueous solution, and the mass concentration of the first precipitant is 20 to 50 wt%; and / or, the pH of the hydrothermal reaction is 9.5 to 11.5; and / or, the temperature of the hydrothermal reaction is 100 to 200° C., and the time of the hydrothermal reaction is 8 to 12 hours; And / or, the solid content of the second slurry is 200-600 g / L.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step S3, the specific surface area of the first precipitate is 2 to 5 m 2 / g; and / or the tap density of the first precipitate is 1.6 to 2.2 g / cm 3 ; and / or the D50 particle size of the first precipitate is 2.5 to 6.0 μm; And / or, the first base liquid is a mixed solution of sodium hydroxide and ammonia water, the pH value of the first base liquid is 12.0-13.0, and the concentration of ammonia water in the first base liquid is 0.3-1.5 g / L; and / or, the total molar concentration of metal ions in the first metal salt solution is 1.0 to 3.0 mol / L; and / or, the first precipitant is a metal hydroxide aqueous solution, preferably the metal hydroxide aqueous solution is selected from any one or more of a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, and a lithium hydroxide aqueous solution; and / or the mass concentration of the first precipitant is 20 to 50 wt%; and / or, the pH value of the first coprecipitation reaction is 11.50 to 12.50, and / or the temperature of the first coprecipitation reaction is 40 to 80° C.; And / or, the first complexing agent is an 8-20 mol / L ammonia solution, and preferably the total mass concentration of the ammonia solution added to the first coprecipitation reaction by the first complexing agent is 0.6-2.5 g / L.
8. The preparation method according to any one of claims 4 to 7, characterized in that In the step S4, the ratio of the total molar amount of nickel ions, cobalt ions, and manganese ions in the first metal solution to the molar amount of lithium ions in the first lithium salt is 1:1.0-1.20; and / or, the modifying additive is selected from any one or more of zirconium oxide, aluminum oxide, tungsten oxide, niobium oxide, strontium carbonate, calcium carbonate, cobalt hydroxide, titanium oxide and magnesium oxide; and / or, the mass of the modifying additive is 0.01% to 1% of the mass of the first precipitate; and / or, the temperature of the first sintering is 700-1000° C., and the holding time of the first sintering is 8-17 hours; And / or, the Rockwell hardness of the ternary positive electrode material is 10 to 40 HRC.
9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method also includes a preparation process of the core of the ternary positive electrode material, and the preparation process includes: In an inert atmosphere, a second coprecipitation reaction is performed on raw materials including a second metal solution, a third precipitant, a second complexing agent and a second base solution to obtain ternary precursor particles; In an oxygen atmosphere, a raw material including the ternary precursor particles, a second lithium salt and an additive is subjected to a second sintering to obtain the ternary positive electrode material core; The specific surface area of the ternary precursor particles is 20 to 80 m 2 / g, and the tap density of the ternary precursor particles is 0.9-1.8 g / cm 3 , the average particle size D50 of the ternary precursor particles is 8.0 to 17.0 μm; and / or, the total molar concentration of metal ions in the aqueous solution of the second metal salt is 1.0 to 3.0 mol / L, and the ratio of the total molar amount of nickel ions, cobalt ions, and manganese ions in the second metal solution to the molar amount of lithium ions in the second lithium salt is 1:1.0 to 1.20; And / or, the second base liquid is an ammonia solution, and the concentration of the second base liquid is 0.02-0.5 mol / L; And / or, the third precipitant is a sodium carbonate solution and / or a potassium carbonate solution, and the concentration of the third precipitant is 4 to 10 mol / L; And / or, the second complexing agent is an aqueous ammonia solution, and the concentration of the second complexing agent is 5 to 15 mol / L; and / or, the temperature of the second coprecipitation reaction is 40 to 80° C.; And / or, the additive is selected from any one or more of zirconium oxide, aluminum oxide, tungsten oxide, niobium oxide, strontium carbonate, calcium carbonate and cobalt hydroxide, and the mass of the additive is 0.01% to 1% of the mass of the ternary precursor particles; And / or, the temperature of the first sintering is 500-800° C., and the time of the first sintering is 5-12 hours.
10. The preparation method according to any one of claims 4 to 9, characterized in that: The preparation method further comprises: In an oxygen-containing atmosphere, performing a third sintering on the raw material including the first sintered product obtained in step S4 and the coating agent to obtain the ternary positive electrode material; Wherein, the coating agent is selected from any one or more of zirconium oxide, titanium oxide, cobalt oxide, boric acid, aluminum oxide and tungsten oxide; and / or, the mass of the coating agent is 0.01% to 1% of the mass of the first precipitate; and / or, the oxygen concentration of the oxygen-containing atmosphere is 85 to 100%; and / or, the temperature of the third sintering is 250 to 800°C, and the time of the third sintering is 3 to 8 hours.
11. A lithium ion battery, characterized in that: It comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode material, and is characterized in that the positive electrode material is the ternary positive electrode material according to any one of claims 1 to 3.
Citation Information
Patent Citations
All-solid-state lithium battery employing core-shell structure high-nickel positive electrode material and preparation method of all-solid-state lithium battery
CN107732193A
High-power positive electrode material with specific core-shell structure and preparation method of high-power positive electrode material
CN113903901A
Precursor for inhibiting microcracks of positive electrode material as well as preparation method and application of precursor
CN114590846A
Positive electrode material precursor, preparation method thereof and positive electrode material
CN115520904A
Positive electrode material and preparation method and application thereof
CN116598458A
Cited By
Composite positive electrode material precursor and preparation method thereof, positive electrode active material and battery
CN121361846A